CompTIA CySA+ Practice Tests, 2nd Edition - Chapple, Mike; Seidl, David (Sybex, 2020)
Efficiently prepare yourself for the demanding CompTIA CySA+ exam CompTIA CySA+ Practice Tests: Exam CS0-002, 2nd Edition offers readers the fastest and best way to prepare for the CompTIA Cybersecurity Analyst exam. With five unique chapter tests and two additional practice exams for a total of 1000 practice questions, this book covers topics including: Threat and Vulnerability Management Software and Systems Security Security Operations and Monitoring Incident Response Compliance and Assessment The new edition of CompTIA CySA+ Practice Tests is designed to equip the reader to tackle the qualification test for one of the most sought-after and in-demand certifications in the information technology field today. The authors are seasoned cybersecurity professionals and leaders who guide readers through the broad spectrum of security concepts and technologies they will be required to master before they can achieve success on the CompTIA CySA exam. The book also tests and develops the critical thinking skills and judgment the reader will need to demonstrate on the exam.